2012
DOI: 10.3928/1081597x-20120823-02
|View full text |Cite
|
Sign up to set email alerts
|

Initial Surface Temperature of PMMA Plates Used for Daily Laser Calibration Affects the Predictability of Corneal Refractive Surgery

Abstract: The temperature of PMMA plates for clinical laser calibration should be controlled ideally within a range of approximately ±5°C, to avoid visually significant refractive error due to calibration error. Further experimental investigations are required to determine the influence of different initial corneal temperatures on the refractive outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…It is important to observe that, in the current study, the ocular surface temperature was measured using a high speed infra-red camera with a frame-rate of 350 images per second and a 750 Hz excimer laser, i.e., the camera was capable of capturing almost every second pulse. This is important as the highest frame rate of the camera reportedly used in similar experiments till date was 50 frames per second 6, 7, 18, 19. Despite the high speed, high resolution and high accuracy of the infrared camera, errors in the measurements and inferences may appear from the errors in the estimation of the emissivity factor of human cornea (∼0.9), estimation of the change of the emissivity factor of human corneas with the corneal curvature, viewing angle of the camera, precise position of the eye as the eye moves during measurement, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to observe that, in the current study, the ocular surface temperature was measured using a high speed infra-red camera with a frame-rate of 350 images per second and a 750 Hz excimer laser, i.e., the camera was capable of capturing almost every second pulse. This is important as the highest frame rate of the camera reportedly used in similar experiments till date was 50 frames per second 6, 7, 18, 19. Despite the high speed, high resolution and high accuracy of the infrared camera, errors in the measurements and inferences may appear from the errors in the estimation of the emissivity factor of human cornea (∼0.9), estimation of the change of the emissivity factor of human corneas with the corneal curvature, viewing angle of the camera, precise position of the eye as the eye moves during measurement, etc.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first paper to clinically document ocular surface temperature changes at high repetition rate of 750 Hz (Previous clinical studies have documented temperature changes up to 500 Hz) 7, 10. In addition, this is the first study to use a high resolution infrared thermal camera with a high frame-rate of 350 images per second allowing capture of thermal images after almost every other laser spot (previous studies have used much lower frame rates of up to 50 frames per second) 6, 7, 18, 19…”
Section: Introductionmentioning
confidence: 92%
“…Es importante efectuar una calibración diaria del láser, la cual consiste en realizar una ablación en un plato de prueba de plástico de material PMMA. Estudios científicos indican que la temperatura ideal de las placas de PMMA debe estar comprendida entre ±5 ºC para evitar fallos de refracción visualmente significativos debido al error en la calibración (Wernli, Schumacher, Wuellner, Donitzky y Mrochen, 2012).…”
Section: Mantenimientounclassified
“…Vetrugno et al 24 reported that "high-repetition-rate excimer laser systems require spot sequences with optimized temporal and spatial spot distribution to minimize the increase in OST." Wernli et al 25 evaluated the effects of initial surface temperature of poly-methyl-methacrylate (PMMA) plates used for daily laser calibration. They found that the ablation depth increased linearly from 73.9 to 96.3 μm within a temperature increase from 10.1°C to 75.7°C (increase rate of 0.3192 μm∕K).…”
Section: Introductionmentioning
confidence: 99%